Chaotic Oscillation Control Model of Power System Under Electromechanical Power Disturbance - Hu, Qiankun (Frontiers in Energy Research, 2022)
In order to stabilize the power system, control the influence of electromechanical power on the power system. The author establishes a fourth-order power system model with a power disturbance term, based on the dissipative property, the possibility of the existence of the system chaotic attractor is analyzed, using Lyapunov exponent spectrum, bifurcation diagram, phase diagram, spectral entropy, etc., the influence of the power disturbance term on the motion state of the system is studied, it can be seen that under the influence of the disturbance frequency, the system will exhibit more abundant dynamic behavior. The parameters of the power disturbance term are more sensitive to the influence of the system power angle, when the disturbance amplitude reaches a certain value, the power angle will increase sharply and eventually the system will become unstable. The experimental results show that the controller parameter is selected, =0.01， =0.3， =0.001. Choose 2 groups of different control objectives r=1.2+0.1sin(t) and r=1.2, it can be clearly seen that the power angle in the system is very unstable before the controller is connected, the fluctuations are large and irregular, after the controller is added for 150s, the power angle tends to be stable, the fluctuation range is small and regular, and the system has almost no chattering. In order to reflect the superiority of the author's control method, under the same parameter conditions, the symbolic function is used as the switching function of the controller, and the tracking control numerical simulation is carried out for the same control objective r=1.2+0.1sin(t) and r=1.2, the controller that adopts the relay characteristic function as the switching function has better control effect, and the system is smooth and stable without chattering.